A LABORATORY STUDY of EFFECTS of TWO FUNGICIDES and SALICYLIC ACIDE on CROWN and ROOT ROT on TOMATO PLANTS - حيدر, ِعفراء; عصام علاف,; محمد طويل, (Latakia University Journal -Biological Sciences Series, 2025)
This research was carried out in a laboratory to test the effect of two fungicides hymexazole and tolclofose-methyl at concentrations of 100, 10, 1, 0.1, and 1000 ppm, and salicylic acid at concentrations of 100, 10, 1000 ppm on croissance, and spores germination percentage for isolate FORL13 (Gene Bank accession number PP213248) of the fungus Fusarium oxysporum f. sp. radicis lycopersici Jarvis and Shomaker (FORL), the cause of root and crown rot of tomatoes. The study showed: 1). The effect of the three chemical compounds on the croissance varied, as the pesticide hymexazole was superior to the pesticide tolclophos-methyl in preventing the growth of fungal hyphae, especially at the two concentrations of 10 and 100 ppm, and the two pesticides were superior to salicylic acid at both concentrations of 10 and 100 ppm. .2). The three compounds had a negative effect, to varying degrees, on spores germination percentage, as the pesticide tolclophose- methyl was superior in preventing the germination of spores of the pathogenic fungus over the two tested compounds. The rate of preventing germination reached 95.3% compared to the control at a concentration of 100 ppm under the influence of the pesticide tolclofose-methyl, while it did not exceed 60% under the influence of salicylic acid and the pesticide Hymexazole.